Шлюбний договір як різновид цивільних договорів у сімейному праві України - Гофман, Ю. В.; Gofman, Ju. (Одеса : Юрид. л-ра, 2014)
The article analyzes the prenuptial agreement (marriage contract) as a special kind of civil law contract. Special attention is drawn to the specific features of this contract, which are inherent in a family law transaction. Subjects, object and the complex nature of the marriage contract are considered in detail.
Гофман Ю. В. Шлюбний договір як різновид цивільних договорів у сімейному праві України / Ю. В. Гофман // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 287-292.
Keywords: договір; цивільний договір; шлюбний договір; суб’єкти договору; зміст договору; предмет договору; об’єкт договору; специфічні ознаки договору; договор; гражданский договор; брачный договор; субъекты договора; содержание договора; предмет договора; объект договора; специфические признаки договора; contract; civil contract; prenuptial agreement; subjects of the contract; content of the contract; subject matter of the contract; object of the contract; specific features of the contract